Metode Pembelajaran Team Accelerated Instruction (Tai) untuk Meningkatkan Mathematic Engagement pada Siswa Sekolah Dasar - Fani Eka Nurtjahjo; Supra Wimbarti (JIP (Jurnal Intervensi Psikologi), 2015)
Mathematics at school often assumed as a terrify. It could affect in mathematics engagement which had an important role in students learning performance. This research was aimed to examine the effect of Team Accelerated Instruction (TAI) toward Mathematic Engagement among 3th to 6th grade of elementary school. This research used pretest-postest control group design. The research showed that TAI could increase mathematics engagement significantly.Keywords: active learning, engagement behavior, mathematics